Peculiarities of Nutrition, Health Education And Leisure of Pre-School Age Children - Liuda Radzevičienė; Lina Miliūnienė; Ilona Dobrovolskytė; Vilma Navickienė; Renata Jadlauskienė; Renata Jarašūnienė; Turan Tolga Vuranok (Social Welfare: Interdisciplinary Approach)
The aim of the research – to assess the nutrition, health education and leisure of pre-school age children. The study involved 3549 children of pre-school education institutions in Šiauliai. A questionnaire survey was selected as the main tool for the research. The research was conducted on the basis of the quantitative research methods. Questionnaires were distributed to and completed by parents. Questionnaire data were processed, analyzed and provided using graphical representation.